Further Reflections on Zhi Qian’s Foshuo Pusa Benye Jing: Some Terminological Questions - Han, Jaehee (Religions, 2021)
Zhi Qian (支謙, fl. ca. 220-257 CE), a prolific Yuezhi-Chinese translator of Indian Buddhist scriptures into Chinese, is widely known for his broad range of styles and terminology. For several decades, his translation activities and his legacy in the history of Chinese Buddhist literature have been a rich field of research, particularly within the context of the transmission of Buddhism from India to China. In the present article, as a follow-up study to “Buddhism for Chinese readers: Zhi Qian’s Literary Refinements in the Foshuo pusa benye jing,” recently published by the authors in this journal, we offer additional reflections on distinctive features of Zhi Qian’s language. We focus on four unusual and interesting renderings in the Foshuo pusa benye jing (佛說菩薩本業經, T. 281), namely (1) santu 三塗; (2) shezui 捨罪; (3) kong 空, wu xiang 無想 and bu yuan 不願; and (4) sishi buhu 四時不護. Through an analysis of these words and phrases, we discuss Zhi Qian’s translation techniques and lexical idiosyncrasies, highlighting their significance in our understanding of the dynamics of language contact and change in the early period of the Chinese Buddhist tradition. Thus, the paper investigates some key Buddhist terms as coined by the early translators on the basis of the classical Chinese and illustrates the semantic changes of the Chinese language taking place in the period as well as influence of Buddhist regimes of knowledge.